Basic reproduction number for the Brazilian Spotted Fever. (7th December 2018) - Polo, Gina; Labruna, Marcelo B.; Ferreira, Fernando
Highlights: R0 calculation is crucial to design control interventions. There is a low impact of larvae population in the maintenance of R. rickettsii . Disease transmission between nymphs/adults and capybara is the major contributor to changes in the R0 . Brazilian Spotted Fever control strategies should focus on the nymphs and adult seasons. Abstract: Brazilian Spotted Fever (BSF) is an emerging and lethal disease in South America which basic reproduction number ( R 0 ) is unknown. Calculating R 0 for this disease is crucial to design control interventions and prevent human deaths. BSF endemic areas are related to the presence of capybaras Hydrochoerus hydrochaeris, amplifier hosts of Rickettsia rickettsii and primary hosts of the tick Amblyomma sculptum, main vector of the agent in this area. Because of the complexity of its dynamics, we calculated R 0 for the BSF system by constructing a next-generation matrix considering different categories of vectors and hosts. Each matrix element was considered as the expected number of infected individuals of one category produced by a single infected individual of a second category. We used field and experimental data to parameterize the next-generation matrix and obtain the final calculation ( R 0  ≈ 1.7). We demonstrated the low impact of the matrix elements corresponding to the transovarial transmission and the transmission from infected larvae in the maintenance of R. rickettsii . Sensitivity and elasticity analyzes were performed to quantify the perturbations of each matrix element in R 0 . We noted that the elements equivalent to the number of infected attached nymphs produced by an infected capybara, and the number of infected capybaras produced by an infected attached nymph or adult are the major contributors to changes in R 0 . Our results provide insights into the strategic design of preventive interventions in BSF endemic areas.